Early results of the Axium MicroFX for Endovascular Repair of IntraCranial Aneurysm (AMERICA) study: a multicenter prospective observational registry. (11th September 2013) - Fargen, Kyle M; Blackburn, Spiros; Carpenter, Jeffrey S; Jabbour, Pascal; Mack, William J; Rai, Ansaar T; Siddiqui, Adnan H; Turner, Raymond D; Mocco, J
Abstract : Background: Axium MicroFX coils contain polymer (polyglycolic/polylactic acid, PGLA) microfilaments designed to significantly impact intra-aneurysmal flow and to encourage aneurysm thrombosis. To provide preliminary evaluation of the safety and suggested efficacy of the MicroFX design, we performed a multicenter prospective single-arm trial, Axium M icroFX for E ndovascular R epair of I ntraC ranial Aneurysm study (AMERICA). Methods: AMERICA is a prospective multicenter 100 aneurysm observational study evaluating the safety and efficacy of Axium MicroFX PGLA coils. Enrollment was started in April 2010 and completed in October 2012. Results: 99 patients underwent treatment for 100 aneurysms at 13 centers. Mean age was 60.2 years, most were women (72%) and 18% of patients had previously undergone treatment for a separate aneurysm. 22% of patients underwent treatment after acute aneurysmal subarachnoid hemorrhage (SAH). Of these patients, all were Hunt and Hess grade 1–3. Pre-procedure modified Rankin score (mRS) was 0–2 in 92% of patients. The majority of aneurysms were anterior circulation (86%), with the most common aneurysm locations being the anterior communicating artery (23%) followed by the supraclinoid internal carotid artery and posterior communicating artery (18% each). The mean maximum diameter was 6.5 mm. Axium MicroFX coils could be placed in all but one treatment (99%). Raymond grade at conclusion of coiling was I (complete) in 52%, II (dog ear or residual neck) in 33% and III (residual aneurysm) in 15%. Discharge mRS was significantly worse in patients with SAH (62% mRS 0–2) compared with electively treated aneurysms (mRS 0–2 in 94%, p<001). Major events were uncommon (6% thromboembolic events, 3% intraoperative vessel or aneurysm rupture) and device-related adverse events (AE) were rare (2% of cases). Conclusions: This prospective study of Axium MicroFX coils demonstrates excellent aneurysm occlusion rates. 52% of aneurysms were completely occluded post-procedure. Within the ruptured aneurysm group, post-procedure occlusion rates were 63.6%. Major AE rates were consistent with historical data.